0710 Sleep EEG Spectral Power Characteristics According to Age and Gender in Middle-to-Late Adulthood. (27th April 2018) - Yoon, J; Lee, E; Lee, S; Jung, K; Park, S; Shin, C; Thomas, R; Yun, C
Abstract: Introduction: The study of electrocortical activity during sleep can provide unique insights into brain health and aging. Epidemiological investigations of EEG power dynamics at the population level are scarce. The main purpose of this study is to examine the impact of age and gender on sleep EEG spectral power in middle-to-late adulthood. Methods: Our study sample is 471 adults (mean age 57.67 ± 6.24, 44.8% male) from an ongoing prospective population-based cohort study, the Korean Genome and Epidemiology Study, who underwent overnight portable sleep study and were free of obstructive sleep apnea or parasomnias. We performed spectral power analysis on a single channel EEG (C4-A1), and analyzed the differences in the absolute and relative power in specified frequency band by age and gender. The EEG power was reported in micro volt-square instead of a percentage or proportion metric. The Kruskal-Wallis test and Chi-square tests were performed for comparisons of sleep EEG spectral power according to age and gender. Results: Relative power decreased in the delta band, but increased in alpha, sigma and beta bands, with age, in the whole night quantitative EEG analysis. With advancing age, the delta band attenuated and the high frequency powers including alpha, sigma and beta increased during REM sleep, in relative EEG power. Surprisingly, no significant effect of age in our categories was observed in all power bands during NREM sleep. The direction of changes of spectral power was similar in both genders, with a decrease in the slow band and increase in faster activity, but more prominent in men. The absolute EEG spectral power over the entire period of sleep showed increases in beta, beta1 and beta2 activity. However, there was lack of any substantial difference in absolute EEG spectral power during REM and NREM sleep. Conclusion: The characteristics of sleep EEG spectral analysis in middle-to-late adulthood differ, more so in males. Some of our results differ from that previously reported in Caucasians, any may reflect racial differences. For example, conventional slow wave sleep is less in Koreans. Support (If Any):